SYATAHAT OF THE SUFIS AND THE ISSUE OF HUMAN CONSCIOUSNESS - Dzikrullah Zulkarnain (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2018)
ABSTRACTThis research empasizes on digging the consept of Syatahat of Sufis where several tasawuf companion showed their psychological condition up on paradoct position, switces themselves on God position. Then, trought researching on Syatahat of Sufis in psychological approach, researcher found several conclusions; i.e. (a) etimologically, Syatahat means shaking (al-harakah); (b) terminologigally, Syatahat of Sufis means any speeches that stranged to be heard by its audience when Sufis reached wajd or wujud level. The factors that force the Sufis said Syatahat were: (1) the strong emotional feelings and rumbled spiritual extasy (wajd), (2) experiences self unification (ittihad), (3) Sufis are in extacy condition (sakr), (4) Sufis hear the signal of divinity within them who invites self-union, so they positioned himself as God, and (5) they loss of self-consciousness; Additionally, the researchers added the other factors, i.e. (1) the Sufis movement comes from tawajud (salat, dhikr, meditation, contemplation, thought) on to the wajd or ecstasy level, (2) when Sufis heart is suddenly controlled by Allah Almighty (warid al-ilahiyyah), so he was no longer able to control their consciousness, and (3) absence of prejudice that the Sufis are united with God, because when that feeling comes, then they really had split (infisal). In other hand, Syatahat of Sufis in psychological perspective, this study focused on transpersonal psychology, researchers tried to draw the conclusion that remarks Syatahat in grammatical word used is a combination of words which are not common to say by common, because the context is only for Allah. Those unusual utterances are manifestation of Sufis psychology themselves, when saying syatahat , Sufis do not realize whatever they have been said.",